Treasury finance and development banking a guide to credit, debt, and risk - Mazzi, Biagio (Hoboken, New Jersey John Wiley & Sons, 2013)
Before the credit crisis, credit was primarily considered only when dealing with counterparty credit risk, high-yield debt, or credit-linked derivatives. Credit and credit risk now permeate every corner of the financial world. This book analyzes credit from the beginning--the point at which a borrowing entity decides to raise capital through its treasury operation. The author delves into the crucial functions that treasury funding plays in the operations of financial institutions, governments, and corporations. More importantly, he clearly demonstrates the various ways that treasury funding affects how financial activities are assessed, transactions are priced, and financial risks are managed.
An introductory view to banking, development banking, and treasury -- Curve construction -- Credit and the fair valuing of loans -- Emerging markets and liquidity -- Bond pricing -- Treasury revisited -- Risk and asset liability management -- Conclusion.
Includes bibliographical references (pages 283-287) and index.
Keywords: Credit; Bank loans; Debt; Financial risk; Development banks